Contextual influences on youth athletes' development and enjoyment - Santos, A.; Diogo, F.; Goncalves, C. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The youth in development suffer influences from the context were is inserted (Bronfenbrenner, 1999), having the sport programs a potential to promote positive youth development (Urban, Lewin-Bizan, & Lerner, 2009). For adhesion and maintenance in sport the enjoyment is consider a major factor (Scanlan, Carpenter, Lobel, & Simons, 1993). The purpose of this study is to verify the influences of different contexts, type of organization and demographic, in youth sport enjoyment and positive development. Method: Three Portuguese soccer clubs of different contexts (one professional club (PC) and two amateur - one of rural area (RAC), other of urban area (UAC) were selected. And the athletes (n=225), with ages between 12 and 18 (15.06±1.64), respond to the Sources of Enjoyment in Youth Sport Questionnaire, Sport Attitudes Questionnaire and Development Assets Profile. To select the professional club it was used the criteria of being on the Portuguese Professional Soccer League. For the amateur ones, it was a district competition level, and the case of urban and rural, the demography, accessibilities and local economy base. For the data analyses it was performed a MANOVA and LSD post-hoc test. Results: The dependent variables are influenced by club context (25%, p=.000) and the age echelon (15%, p=.001). The groups showed significant differences by club and echelon in the peers affiliation (p=.009; p=.001), convention (p=.000), effort (p=.000, p=.002), support (p=.002, p=.034), learning commitment (p=.010, p=.045) and familiar (p=.006, p=008), having the RAC athletes register the lower scores. Conclusions: This shows that the athletes practice context influences some variables of the sports attitudes, the sources of enjoyment and the development assets. Also, the PC and UAC athletes` characteristics are more similar between themselves than with RAC. The RAC context appears a disadvantage factor for positive developmental, maybe due to organizational or local context.